(untitled) (Journal of Hama University, 2022)
Our study aimed at knowing the spread percentage of Toxoplasmosis among women and cats in Damascus where a plasma analysis under Latex Test has been done for 225 samples (115 of them were women auditors at Ibn Alnafis Hospital in Damascus, and 110 of cats visiting veterinary clinics in Damascus). Affliction with Toxoplasmosis ,in general , among the women tested reached the percent 40,86%), and the women who have contact with cats (27,83%), while the spread percentage among women who didn’t show any affliction nevertheless in contact with cats ,was (21,74%). Although the spread percentage was among women who showed affliction with the contact with cats (13,04%),and the spread percentage among women who didn’t show any affliction with the contact with cats (37,93%). While the spread according to the age groups of the women tested which were divided into four age groups with a difference of ten years in average between a group and the other , in the first section the spread percentage reached (24%), in the second (41,93), in the third (48,71%) and in the fourth (45%).As for the place of affliction , the spread percentage in the northern part reached (47,61%),in the southern area (57,59%),in the eastern area (24,13%) and in the Western area (27,77).The percentage of the women afflicted by Toxoplasmosis who suffered from former abortion was (7,82%),If we know that not all the abortions were a result of Toxoplasmosis , the spread percentage among cats reached (58,18%) because it has been improved that cats breeding and contact with them , as well as place residence play a great role in the increase of affliction among women .